(untitled) (Colombia Medica, 2018)
Introduction: Primary stabbing headache (or “ice pick headache”) is an alteration characterized by brief jabs (short stabs of pain, lasting 3 seconds), which appear spontaneously, irregularly, and affecting unilaterally or bilaterally. Indomethacin has traditionally been used as the main therapeutic option. However, this drug is ineffective in a considerable percentage of patients and can generate multiple adverse effects that occur at therapeutic doses. Clinical case: A 7-year-old male patient with primary stabbing headache of mild to moderate intensity, lasting 3 to 4 seconds, without relevant history, with normal neurodevelopment, neurological examination and neuroimaging; no triggers were identified. It was started therapeutic trial with Coenzyme Q10; however, no improvement in the symptoms was identified. Treatment and outcomes: A therapeutic management was carried out with Melatonin, which led to complete remission of the symptoms; without adverse effects in the posterior follow-up months. Clinical and scientific relevance: There is little information regarding effective and safe treatments for primary stabbing headache in children. The present case identifies Melatonin as an innovative, effective and safe therapeutic alternative in the treatment of primary stabbing headache in children. This is a significant advance in the understanding of primary stabbing headache in the pediatric population. Conclusion: Melatonin may be an effective and safe therapeutic option for the treatment of primary stabbing headache in pediatric patients. It is necessary to deepen its research, in order to establish its use in a clinical practice guide.